Impact of Prevalence of Substance use and its health issues on the behavioural pattern of students in HEIs with reference to Chennai - Novaleena, S.Jebaseeli; G.Kannan, G.Kannan (Journal of Neonatal Surgery, 2025)
(Pose, 1996)1 defined Substance or drug as anything that has the potential of causing addiction, habituation or altered consciousness. It can also be defined as any chemicals that can change the structure or function of the body. This research was conducted among the students of HEI s in Chennai with the objectives such as To identify the common drugs abused by students on college campuses, To find out the causes of substance abuse by college students, To find out the route of administration of substance, To study the link between substance abuse and behavioural pattern of college students, To investigate the influence of health education (Normative Reeducation) on prevention of drug abuse among the affected students. Research was conducted among the students of HEI’s with respect to Chennai during the time period October 2024 to December 2025. The Questionnaire was used to collect the data from 386 respondents and it was analyzed using the statistical tools. The Conceptual framework was framed.